2016
DOI: 10.1063/1.4947220
|View full text |Cite
|
Sign up to set email alerts
|

The structure of a magnetic-field front propagating non-diffusively in low-resistivity multi-species plasma

Abstract: We report on the first experimental verification of the traveling-wave-like picture of a magnetic-field and an associated electric potential hill propagating non-diffusively in low resistivity plasma. High spatial resolution spectroscopic method, developed here, allowed for obtaining the detailed shape of the propagating magnetic-field front. The measurements demonstrated that the ion separation, previously claimed, results from the reflection of the higher charge-to-mass ratio ions from the propagating potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…This assumption is supported by recent measurements, 39 showing that the electric-and magnetic-front profiles remain nearly constant during their propagation at the relevant time-scale of the measurement. The force exerted on an ion by such an electric field is proportional to the ion's charge; hence the ion's velocity change (in time) is proportional to its charge-to-mass ratio, Z/m.…”
Section: B Density Evolution During the Plasma-magnetic Field Interasupporting
confidence: 71%
“…This assumption is supported by recent measurements, 39 showing that the electric-and magnetic-front profiles remain nearly constant during their propagation at the relevant time-scale of the measurement. The force exerted on an ion by such an electric field is proportional to the ion's charge; hence the ion's velocity change (in time) is proportional to its charge-to-mass ratio, Z/m.…”
Section: B Density Evolution During the Plasma-magnetic Field Interasupporting
confidence: 71%
“…2001; Rubinstein et al. 2016) showed that there is also a significant ion motion. Moreover, they demonstrated a most interesting process; ion separation in a multi-ion species plasma.…”
Section: Discussionmentioning
confidence: 99%
“…2004, 2008; Rubinstein et al. 2016), showed magnetic field penetration that was much faster than expected by classical resistivity. Theorists at the Kurchatov Institute (Kingsep, Mokhov & Chukbar 1984; Kalda & Kingsep 1989; Kingsep, Chukbar & Yan‘kov 1990; Gordeev, Kingsep & Rudakov 1994) and in other research groups (Fruchtman 1991, 1992 a , b ; Fruchtman & Gomberoff 1992, 1993; Fruchtman & Rudakov 1992, 1994; Oliver et al.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations